Application of Progressive Web Apps (PWA) on PT SKA’s E-Commerce Website - Evangeline Eunike; Ridwan Sanjaya; Albertus Dwiyoga Widiantoro (Soegijapranata Catholic University, 2023)
Mobile app developers are often overwhelmed when they must create mobile applications, which must create applications for iOS and Android users. The problem is that each one has a different programming language, for iOS users it must be developed with Objective-C or Swift while for Android it is developed with Kotlin or Java programming language. This research was conducted with a tool that in the research process using observation. Observations were made by testing native applications with applications that were already using Progressive Web Apps (PWA) using the PageSpeed Insights tool. Progressive Web Apps (PWA) help optimize websites so that they look like native applications both on computers and on mobile. Application can be accessed offline, provide notifications, and there is no need to download application on the PlayStore or App Store, just through the website. This PWA exists to address these issues. PWA makes things faster and optimizes quality.